Clinicopathological study of skin tumors - Unnikrishnan, Neetha; Letha V (Asian Journal of Medical Sciences, 2024)
Background: The diagnosis of skin tumors can cause difficulties due to their wide variety of overlapping differentiation and complicated nomenclature. Histopathological study is the most valuable means of diagnosis. Keeping in view these facts, an attempt is made to study the different varieties of tumors of the skin. Aims and Objectives: (1) The aim of this study was to study the histomorphology of different skin tumors with ancillary technique necessary and to correlate with the clinical features. (2) To find the proportion of various skin tumors. (3) To classify and identify various skin tumors and study its variation according to age, sex, site, etc., which will bear an impact on patient management and prognosis. Materials and Methods: This observational study included all cases of skin tumors received in the Department of Pathology, Kottayam Medical College, during a period of 1 year. Biopsy samples were collected, fixed in 10% formalin, processed and embedded in paraffin blocks, and stained with hematoxylin and eosin (H and E). The stained sections were studied under a microscope and histopathological diagnosis was correlated with clinical diagnosis. Results: Out of the 227 cases of skin tumors, 102 (44.9%) were male and 125 (55.1%) were female. The incidence of skin tumors peaks in individuals older than 60 years of age. The most common sites affected were face (40%). Keratinocytic tumors constituted the largest proportion of tumors (43%), followed by melanocytic tumors (31%), soft-tissue tumors (13%), appendage tumors (11%), neural (1%), and hematolymphoid tumors (1%). Conclusion: Out of the 227 cases in the present study, the clinical diagnosis of only 169 cases was correlating with the histopathological diagnosis. This emphasizes the role of microscopy in the correct diagnosis of skin tumors.